Effects of Ecosystem Recovery Types on Soil Phosphorus Bioavailability, Roles of Plant and Microbial Diversity: A Meta‐Analysis - Jinguo Hua; Wenyue Wang; Jinyu Huo; Lin Wu; Lingfeng Huang; Hongtao Zhong (Ecology and Evolution, 2025)
ABSTRACT Strategies for restoring degraded ecosystems vary widely in the levels of human intervention. It has commonly been assumed that recovery with artificial inputs would be quicker and more efficient. However, is this truly the situation? We conducted a meta‐analysis to evaluate the differences and applicability between ecological restoration and ecological rehabilitation. Relationships between soil phosphorus content, plant diversity, and soil microbial diversity were analyzed using 463 valid experimental data points collected from 72 publications. The results indicated that in grassland ecosystems, ecological restoration outperformed rehabilitation by 35%, 68%, 38%, and 48% in belowground biomass, community coverage, plant richness, and Shannon diversity, respectively. In forests, rehabilitation trailed behind restoration by 58%, 26%, and 92% in belowground biomass, Simpson diversity, and bacterial Shannon diversity. Furthermore, there was minimal difference in the recovery mode among different fungal and bacterial phyla. Rehabilitation demonstrated lower stability and efficiency in long‐term phosphorus cycling compared to restoration. Overall, ecological restoration offers more stable and efficient long‐term phosphorus cycling, thereby questioning the effectiveness of ecological rehabilitation for sustainable ecosystem recovery, especially for species diversity and phosphorus cycling.